Infections with Neisseria gonorrhoeae and Chlamydia trachomatis in women with acute salpingitis. Issue 3 (June 1985) - Kristensen, G B; Bollerup, A C; Lind, K; Mårdh, P A; Ladehoff, P; Larsen, S; Marushak, A; Rasmussen, P; Rolschau, J; Skoven, I
Abstract : The value of cultural and serological procedures in diagnosing gonococcal and chlamydial infections was investigated in 85 women who had provisional diagnoses of pelvic inflammatory disease. The correlation between certain clinical variables and the absence or presence of such infections was also studied. In 46 the diagnosis of acute salpingitis was verified by laparoscopy. The laboratory and clinical findings in the patients with acute salpingitis were compared with those in the remaining 39 women in whom laparoscopy did not show signs of inflammation. Salpingitis was considered to be gonococcal if Neisseria gonorrhoeae was isolated or a fourfold or more change in titre of antibodies to gonococcus pilus antigen was found. The diagnosis of chlamydial salpingitis was based on the isolation of Chlamydia trachomatis, a fourfold or more change in titre of IgG antibodies to or from a titre of greater than or equal to 1/256, or the presence of IgG antibodies at a titre of greater than or equal to 1/512. Patients with chlamydial salpingitis had less severe symptoms but a more protracted course of disease than patients with gonococcal salpingitis or with acute salpingitis not associated with the two pathogens.